Right Ventricular Outflow Tract Stenting in Tetralogy of Fallot Infants With Risk Factors for Early Primary Repair. (December 2016) - Sandoval, Juan Pablo; Chaturvedi, Rajiv R.; Benson, Lee; Morgan, Gareth; Van Arsdell, Glen; Honjo, Osami; Caldarone, Christopher; Lee, Kyong-Jin
Abstract : Background—: Tetralogy of Fallot with cyanosis requiring surgical repair in early infancy reflects poor anatomy and is associated with more clinical instability and longer hospitalization than those who can be electively repaired later. We bridged symptomatic infants with risk factors for early primary repair by right ventricular outflow tract stenting (stent). Methods and Results—: Four groups of tetralogy of Fallot with confluent central pulmonary arteries were studied: stent group (n=42), primary repair (aged <3 months) with pulmonary stenosis (early-PS group; n=44), primary repair (aged <3 months) with pulmonary atresia (early-PA group; n=49), and primary repair between 3 and 11 months of age (surg>3mo group; n=45). Stent patients had the smallest pulmonary arteries with a median (95% credible intervals) Nakata index (mm 2 /m 2 ) of 79 (66–85) compared with the early-PA 139 (129–154), early-PS 136 (121–153), and surg>3mo 167 (153–200) groups. Only stent infants required unifocalization of aortopulmonary collaterals (17%). Stent and early-PA infants had younger age and lower weight than early-PS infants. Stent infants had the most multiple comorbidities. Stenting allowed deferral of complete surgical repair to an age (6 months), weight (6.3 [5.8–7.0] kg), and Nakata index (147 [132–165]) similar to the low-risk surg>3mo group. The 3 early treatment groups had similar intensive care unit/hospital stays and high reintervention rates in the first 12 months after repair, compared with the surg>3mo group. Conclusions—: Right ventricular outflow tract stenting of symptomatic tetralogy of Fallot with poor anatomy (small pulmonary arteries) and adverse factors (multiple comorbidities, low weight) relieves cyanosis and defers surgical repair. This allowed pulmonary arterial and somatic growth with clinical results comparable to early surgical repair in more favorable patients. Abstract : Supplemental Digital Content is available in the text.